Pemberdayaan Masyarakat dalam Pencegahan Gangguan Gizi Anak dalam Hubungannya dengan Cacingan di Panti Asuhan Kota Dumai: Community Empowerment in the Prevention of Child Nutrition Problems in Relationship with Helminth Infestation in Orphanages Dumai City - Suri Dwi Lesmana; Dedi Afandi; Mislindawati Mislindawati; Mokhammad Raihan Eka Putra; Fatah Abdul Khair (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
Malnutrition is a significant health problem in Indonesia today and is one of the highlights of government programs in the health sector. Nutritional status has a vital role in the growth and development of children and is also closely related to intelligence. Soil-Transmitted Helminths (STH) infestation is a chronic disease that impacts nutritional disorders. One of the community groups that need to be considered in nutritional problems and their relation to intestinal worms is an orphanage. This activity aims to increase community empowerment through education about nutrition and its disorders, STH infestation, and its impact on growth and development. In addition, the nutritional status of the children living in the orphanage will be checked. This activity found that most of the orphanage residents had a low level of knowledge about nutritional disorders and worm infestations, 48.84%. The results of the nutritional status examination showed that most of the orphanage residents had normal nutritional status, but 21.15% were still undernourished.